The neural correlates of self-referential memory encoding and retrieval in schizophrenia. (31st January 2018) - Jimenez, Amy M.; Lee, Junghee; Wynn, Jonathan K.; Green, Michael F.
Abstract: Background: Enhanced memory for self-oriented information is known as the self-referential memory (SRM) effect. fMRI studies of the SRM effect have focused almost exclusively on encoding, revealing selective engagement of the medial prefrontal cortex (mPFC) during "self" relative to other processing conditions. Other critical areas for self-processing include ventrolateral prefrontal cortex (vlPFC), temporo-parietal junction (TPJ) and posterior cingulate/precuneus (PCC/PC). Previous behavioral studies show that individuals with schizophrenia fail to benefit from this memory boost. However, the neural correlates of this deficit, at either encoding or retrieval, are unknown. Methods: Twenty individuals with schizophrenia and 16 healthy controls completed an event-related fMRI SRM paradigm. During encoding, trait adjectives were judged in terms of structural features ("case" condition), social desirability ("other" condition), or as self-referential ("self" condition). Participants then completed an unexpected recognition test (retrieval phase). We examined BOLD activation during both encoding and retrieval within mPFC, vlPFC, TPJ, and PCC/PC regions-of-interest (ROIs). Results: During encoding, fMRI data indicated both groups had greater activation during the "self" relative to the "other" condition across ROIs. Controls showed this primarily in mPFC whereas patients showed this in PCC/PC. During retrieval, fMRI data indicated controls showed differentiation across ROIs between "self" and "other" conditions, but patients did not. Conclusions: Results suggest regional differences in the neural processing of self-referential information in individuals with schizophrenia, perhaps because representation of the self is not as well established in patients relative to controls. The current study presents novel findings that add to the literature implicating impaired self-oriented processing in schizophrenia. Highlights: Enhanced memory for self-oriented information may be lacking in schizophrenia. We examined neural correlates of self-referential memory at encoding and retrieval. At encoding, patients failed to activate core brain regions compared to controls. At retrieval, patients did not differentiate self from other at the neural level. These novel findings further implicate impaired self processing in schizophrenia.